Komunikasi Interpersonal Jarak Jauh Orang Tua dengan Anak Menggunakan Smartphone - Aji Putri, Tantri; , Dr. Ahmad Muhibbin, M. Si (2017)
Abstract This research intens to describe interpersonal communication longdistance between parents and children using Smartphone for college student of Muhammadiyah Surakarta's university. This research using a qualitative approach. Data accumulation using depth interview and documentation. Validty of data using triangulation data and qualitative approach technique. Data analysis using interactive analysis that include data approach, data reductreduction, presentation of data and withdrawal conclution. The results of this research such as 1.) The benefit a.) The increase relatioships between parents and children b.) Observe development of lectures children c) healthty condition d) observe relation between children and their friends e) maintaining openness of children with parents f) observe finance's condition. 2) media usage intensity which connected by distance on this research parents and children have intens enough, they are commonly communicate at least one per day or more by chat. 3) Media that usually in use such as: Whatsapp, Blackberry Messenger, and Line each of them has fitur which could support long distance communication process, almost all informant use the fitur, such as: send images each other, video call, voice note, and share location. 4) the chase of long distance communication on this research, conflicts that they go through are: a) such as lost with no news children forget giving a news to parents; b) unavailability internet coverage or signal from both; c) faultness of miss comunnication and misunderstanding in sending messages; d) the application that have to be updated, which means parents didn't understand with the stuff and almost all the informant solve this long distance problems conflict talking or explaning by phone. Keyword: interpersonal communication, long distance, smartphone